Sym004, a Novel EGFR Antibody Mixture, Can Overcome Acquired Resistance to Cetuximab - Iida, Mari (Neoplasia Press Inc., 2013)
The epidermal growth factor receptor (EGFR) is a central regulator of tumor progression in a variety of human cancers. Cetuximab is an anti-EGFR monoclonal antibody that has been approved for head and neck and colorectal cancer treatment, but many patients treated with cetuximab don't respond or eventually acquire resistance. To determine how tumor cells acquire resistance to cetuximab, we previously developed a model of acquired resistance using the non-small cell lung cancer line NCI-H226. These cetuximab-resistant (Ctx(R)) cells exhibit increased steady-state EGFR expression secondary to alterations in EGFR trafficking and degradation and, further, retained dependence on EGFR signaling for enhanced growth potential. Here, we examined Sym004, a novel mixture of antibodies directed against distinct epitopes on the extracellular domain of EGFR, as an alternative therapy for Ctx(R) tumor cells. Sym004 treatment of Ctx(R) clones resulted in rapid EGFR degradation, followed by robust inhibition of cell proliferation and down-regulation of several mitogen-activated protein kinase pathways. To determine whether Sym004 could have therapeutic benefit in vivo, we established de novo Ctx(R) NCI-H226 mouse xenografts and subsequently treated Ctx(R) tumors with Sym004. Sym004 treatment of mice harboring Ctx(R) tumors resulted in growth delay compared to mice continued on cetuximab. Levels of total and phospho-EGFR were robustly decreased in Ctx(R) tumors treated with Sym004. Immunohistochemical analysis of these Sym004-treated xenograft tumors further demonstrated decreased expression of Ki67, and phospho-rpS6, as well as a modest increase in cleaved caspase-3. These results indicate that Sym004 may be an effective targeted therapy for Ctx(R) tumors.